Religious Programs as Drivers of Spiritual Character in the Pancasila Student Profile: A Case Study at MA Wahid Hasyim Balung Jember - Agustiningsih, Ana Hafifah; Nahrowi, Moh. (Lembaga Aneuk Muda Peduli Umat, Bekerjasama dengan LaKaspia, 2025)
This study examines how religious programs support the development of students’ spiritual character within the framework of the Pancasila Student Profile (Profil Pelajar Pancasila) at MA Wahid Hasyim Balung Jember. Adopting a qualitative case study design, data were collected through observation, interviews, and documentation, and validated using triangulation. The findings reveal that activities such as congregational dhuha prayers (shalat dhuha berjamaah), istighotsah (collective supplication), Qur’an recitation (khotmil Qur’an), and hajj rituals practice (manasik haji) have been routinely implemented and play a role in cultivating discipline, responsibility, and empathy among students. These efforts are supported by institutional commitment, teacher involvement, and family participation. However, the process of spiritual value internalization faces several challenges, including variations in student motivation, limited supervision, social and digital media influences, and inconsistent family support. The study concludes that while religious programs contribute to strengthening spiritual character, ongoing collaboration between schools, families, and the community is needed to address existing obstacles and to enhance character education in Islamic schools.